2008
DOI: 10.1080/01904160801926780
|View full text |Cite
|
Sign up to set email alerts
|

Pulp Fiber Residue and Supplemental Irrigation on Yield and Nutrient Uptake of Potato

Abstract: Organic matter levels combined with drought periods during the growing season have adverse impacts on rain-fed potato production in coarse textured soils of eastern Canada. Using pulp fiber residues (PFR) may build up soil organic matter, improve crops yield and nutrient uptake, and reduce the need for supplemental irrigation in this region. A box experiment with 3 rates of PFR [0, 45, and 90 Mg ha −1 dry mater carbon (C) basis] with or without supplementary drip irrigation was established in a sandy loam soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The highest values of these parameters were obtained when applying organic manure treatment, 40 kg S fed -1 and 16 kg Zn fed -1 . Ofori et al, (2005) and Fahmy et al, (2008) found that the application of organic amendments to all the soils improved uptake of nitrogen. While Pooniyaand Shivay., (2013) found that Zn fertilization had significant effects on the concentrations and uptake of N and K in basmati rice grain and straw (Tables 6 and 8).…”
Section: Data Inmentioning
confidence: 99%
“…The highest values of these parameters were obtained when applying organic manure treatment, 40 kg S fed -1 and 16 kg Zn fed -1 . Ofori et al, (2005) and Fahmy et al, (2008) found that the application of organic amendments to all the soils improved uptake of nitrogen. While Pooniyaand Shivay., (2013) found that Zn fertilization had significant effects on the concentrations and uptake of N and K in basmati rice grain and straw (Tables 6 and 8).…”
Section: Data Inmentioning
confidence: 99%
“…Das et al (2015) reported a similar response of potato height on a different variety. The significantly higher effects of combined organic and mineral fertilizers on yield components of potato might be attributed to their complementary effects, whereby the inorganic fertilizers enable the immediate availability of nutrients while the FYM supply nutrients slowly throughout the growing period and improve the soil properties such as soil porosity and reduced soil acidity (Fahmy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Number of tubers per hill, foliage weight, tuber weights per plant, marketable and unmarketable tubers were determined at harvesting. The characteristics of unmarketable tubers were determined as explained by Fahmy et al (2008) and Kavvadias et al (2012). For potatoes and similar root crops, the yield components are number of stems per plant, number of tubers per plant and average tuber weight (Mengel & Kirkby, 1987).…”
Section: Soil and Plant Samples Collection And Preparationmentioning
confidence: 99%